(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
India is a diverse country, full of ethical and religious diversities. Inspite of these diversities, citizens of India live together peacefully but there are some anti-social elements that keep on disturbing this peaceful spirit of the country to provoke religious sentiments of peace loving people. These activities are commonly known as terror activities. As any terror activity or attack is done with a aim and creation of fear among civilians is one of the most common aim of terrors and media act as an carrier of these thread messages and hence, plays a vital role for the same. Media acts as their best friend as they provide oxygen to these promotions. The relation between the two, that is, media and terrorism is two way go on one hand. Media acts as a carrier of the thread messages and creates an environment of fear among the civilians in return they get vicious and breath taking news headlines which provides hike in the sales and TRP of various news channels. This paper examines the role of media and politicians to become the source of information about terrorism and means of creating threatful environment and sometimes even gaining sympathy for terrorists.